The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fbioe.2022.799443
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Revision Arthroplasty Based on 3-Dimensional Reconstruction Technology Using Jumbo Cups

Abstract: Background: This study was aimed at evaluating the changes in cup coverage (CC) and hip center of rotation (HCOR) in acetabular defects of various severities treated with acetabular revision using jumbo cups.Methods: A total of 86 hips were included. The American Academy of Orthopedic Surgeons (AAOS) classification of these patients was as follows: 16 patients, AAOS I; 16 patients, AAOS II; and 16 patients, AAOS III. A three-dimensional (3D) implant simulation technique was used to visualize the placement of j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…However, if the decreased acetabular offset was not compensate and only the original femoral offset was restored, the global offset will be reduced. Several studies have reported that change of the hip centre affect the biomechanics of the hip 27 , 28 . To maintain global offset, medialization should theoretically be compensated for by an equivalent increase in femoral offset 10 .…”
Section: Discussionmentioning
confidence: 99%
“…However, if the decreased acetabular offset was not compensate and only the original femoral offset was restored, the global offset will be reduced. Several studies have reported that change of the hip centre affect the biomechanics of the hip 27 , 28 . To maintain global offset, medialization should theoretically be compensated for by an equivalent increase in femoral offset 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Computer-aided technology has been successfully applied in orthopedic instrument design, materials and surgical simulation with mature technology applications (12)(13)(14). Previous studies have (15,16) used Mimics software to simulate the reconstruction of a high dislocated acetabulum, with an individualized and precise preoperative design to obtain satisfactory acetabular cup position and coverage and to avoid problems such as iliopsoas impingement.…”
Section: Introductionmentioning
confidence: 99%